PEMANFAATAN SERANGGA HELICOVERPA ARMIGERA UNTUK MENDETERMINASI KEBERADAAN DAN LAJU DEGRADASI TOKSIN BACILLUS THURINGIENSIS CRYIAC DI TANAH = THE USE OF HELICOVERPA ARMIGERA TO DETERMINE THE PRESENCE ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Cotton expressing a Bacillus thuringiensis toxin Cry1 Ac (transgenic cotton) has been planted in South Sulawesi. One of the identified risks is the effect of the toxin resulted from decom¬position of transgenic plants on soil biodiversity. The objectives of this research were to develop a bioassay procedure using larvae of Helicoverpa armigera to estimate the presence and degradation rate of Cryl Ac in soil. Cry/ Ac in 1 ml water was spiked on 1 g soil. The treated soil was mixed with the artificial diet (120 g) during its preparation. The newly hatched larvae were released on diet containing Cry1Ac ranging from 0.1-1,000,000 ng/120 g diet. Observations were made on the 7th day after release by assessing larval mortality, weighing and identifying the instar of surviving larvae. The study on degradation of Cry1 Ac was carried out at the concentrations of 100,000 and 1,000,000 ng with 0-30 days incu¬bation period. Similar bioassay procedures were implemented. Larvae of H. armigera were susceptible to Cry 1 Ac, and using growth inhibition as the end-point observation Cry1Ac could be detected at relatively low concentration. Degradation of Cryl Ac under the condition of 26-29°C and 10:14 L:D was observed to start occurring at the 20th day after incubation. Key words: Environmental risk assessment, Transgenic cotton, Bacillus thuringiensis, Bioindicator, and Helicoverpa armigera